Internet of Sounds (IoS) for soundscape applications - Ong, Wen Hui (Nanyang Technological University, 2024)
Using audio stimuli to improve perceived soundscape quality has been an important point of research in the past 50 years. In recent years, more studies have been done on the effects of dynamic maskers, with constantly changing sounds and volume, on human physiology. An Internet of Sounds (IoS) is needed to achieve the playback of these dynamic maskers. This report is about the Augmenting Urban Soundscapes (AUS) system, an IoS developed by the Digital Signal Processing (DSP) lab, Smart Nation Translational Lab (SNTL), Nanyang Technological University (NTU). It will cover the various functions of the AUS system, as well as the methods used to implement those functions.